Odontogenic myxoma of the maxillary sinus associated with an ectopic tooth - Robert S. Redman; Suman Chauhan; Brian B. Chang; Sonya C. Malekzadeh; Sarah K. Rapoport (Oral and Maxillofacial Surgery Cases, 2025)
Odontogenic myxoma is an uncommon, benign neoplasm that tends to recur because it locally invades or is trapped among the bony trabeculae. It is thought to arise from mesenchymal tissue associated with teeth and periodontium, as it develops in the tooth-bearing area of the jawbones, often in proximity to an unerupted tooth. Occasionally it may displace teeth. Those occurring in the maxilla often invade the maxillary sinuses. We report here a rare case of an odontogenic myxoma of the maxillary sinus associated with an ectopic tooth which was impinging on the nasal mucosa and accordingly was extracted through the nose.